A Pragmatic Study of Implicature in Selected Qur'anic Verses - Alaa’ Abbas Ali; Dr. Mazin Jasim Mohammad (Journal of College of Education, 2025)
This study is devoted to the investigation of the phenomenon of implicature in selected Qur’anic verses from a pragmatic point of view. The study aims at figuring out the pragmatic meaning of implicatures that are found in the selected Qur’anic verses. The study is qualitative in nature and is based on Grice’s (1975) theory of implicatures. (4) Glorious Qur’anic verses have been selected as sample of this study. As a result of the analysis the selected data, it has been proved that the selected Qur’anic verses include different forms of implicature. The selected verses are seen to include a conversational form of implicature, but the conventional form does not exist.
Keywords: Pragmatic, implicature, the Glorious Qur'an